Diversity of change in body mass index and skinfold thickness between different study courses within four years of study among the male students in a university in Poland - Bobula, Gabriel; Czarny, Wojciech; Ignasiak, Zofia; Chakraborty, Raja; Koziel, Slawomir (Anthropological Review, 2022)
Objective: This study examined whether there were significant changes (expectedly increase) in BMI (Body Mass Index), and relative subcutaneous body fat during the four years of study in a university and compared these changes between the students of different courses, viz., Computer science, Law and administration, Humanities and Physical education.Design: This was a prospective follow up study with measurements at two time points with gap of four years. Body mass index, Triceps, subscapular, mid-axillary, abdominal, supra-illiac and medial-calf skinfold thicknesses were measured at two points of time, just after entrance to university and again after completion of four years. Student’s T-test, one-way ANOVA, and repeated measures ANNOVA (two-way) were employed to assess significance of differences in anthropometric measures between groups of students.Setting: The study was conducted at the University of Rzeszów, Poland.Participants: 191 young men university students aged approximately 19.5 years and 24.0 years, at the beginning and after four years, respectively, during this study.Results: Students of all courses underwent increments in BMI, absolute- and relative skinfold thicknesses, except that the students of physical education course did not show change in skinfold thicknesses relative to BMI.Conclusions: It has been concluded that the change in the adiposity profile during the years of study at university varied according to the course types. Further, detailed studies on the nature and cause of such variation occurring between course types may lead to better understanding etiology of overweight and obesity before entering to adult life.